ROS 2018
DOI: 10.20455/ros.2018.849
|View full text |Cite
|
Sign up to set email alerts
|

Neuro- and Hepatoprotective Effects of Methylene Blue in Rats Treated with Lipopolysaccharide Endotoxin

Abstract: The effects of methylene blue (MethyB) on oxidative stress markers in the serum and on the brain and liver tissue damage following lipopolysaccharide (LPS) injection in rats were studied. Rats received intraperitoneal (i.p.) injection of LPS (300 µg/kg) alone or along with MethyB (5 and 10 mg/kg) and euthanized 4 h later. Malondialdehyde (MDA), nitric oxide, paraoxonase-1 (PON-1) activity, cholinesterase activity, and glucose were measured in the serum. The brain and liver histopathology, glial fibrillary acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 55 publications
(66 reference statements)
0
1
0
Order By: Relevance
“…Mayer et al [16] suggested that MethyB acts primarily as a direct inhibitor of nitric oxide synthase, but is only a poor inhibitor of soluble guanylyl cyclase. MethyB has been shown to inhibit the production of nitric oxide via the inhibition of nitric oxide synthases both in vitro and in vivo [16,17] and to decrease brain nitrite/nitrate [39] and serum nitric oxide concentrations [40] .…”
Section: Dmentioning
confidence: 99%
“…Mayer et al [16] suggested that MethyB acts primarily as a direct inhibitor of nitric oxide synthase, but is only a poor inhibitor of soluble guanylyl cyclase. MethyB has been shown to inhibit the production of nitric oxide via the inhibition of nitric oxide synthases both in vitro and in vivo [16,17] and to decrease brain nitrite/nitrate [39] and serum nitric oxide concentrations [40] .…”
Section: Dmentioning
confidence: 99%